Insights Into the Significance of the Chinense Loess Plateau for Preserving Biodiversity From the Phylogeography of Speranskia tuberculata (Euphorbiaceae) - Ye, Jun-Wei; Wu, Hai-Yang; Fu, Meng-Jiao; Zhang, Pei; Tian, Bin (Frontiers in Plant Science, 2021)
The significance of the Chinese Loess Plateau (CLP) in maintaining biodiversity for northern China has rarely been shown, as previous phylogeographic studies are mostly woody species and they have revealed that Quaternary refugia are mainly located in mountain regions. We selected a drought-enduring endemic herb, Speranskia tuberculata (Euphorbiaceae), to determine its glacial refugia and postglacial demographic history. To this end, we sampled 423 individuals from 38 populations covering its entire geographic distribution. Three chloroplast DNA (cpDNA) fragments, two low-copy nuclear genes, and six nuclear microsatellites (nSSRs) were used and supplemented with ecological niche modeling (ENM) to infer the phylogeographic history of this species. Populations with private haplotypes and high haplotype diversity of cpDNA are mainly located in the CLP or scattered around northeastern China and the coastal region. Spatial expansion, detected using a neutrality test and mismatch distribution, may have resulted in a widely distributed ancestral cpDNA haplotype, especially outside of the CLP. For nuclear DNA, private haplotypes are also distributed mainly in the CLP. In nSSRs, STRUCTURE clustering identified two genetic clusters, which are distributed in the west (western cluster) and east (eastern cluster), respectively. Many populations belonged, with little to no admixture, to the western cluster while (hardly) pure populations of the eastern cluster were barely found. Genetic differentiation is significantly correlated with geographic distance, although genetic diversity is uniformly distributed. ENM suggests that the distribution of S. tuberculata has recently expanded northwards from the southern CLP, whereas it has experienced habitat loss in the south. Thus, S. tuberculata populations probably survived the last glacial maximum (LGM) in the southern CLP and experienced post-glacial expansion. Wind-dispersed pollen could bring the majority of genotypes to the front during spatial expansion, resulting in uniformly distributed genetic diversity. Based on evidence from molecular data and vegetation and climate changes since the LGM, we conclude that drought-enduring species, especially herbaceous species, are likely to have persisted in the CLP during the LGM and to have experienced expansion to other regions in northern China.